Trampa - Dyulgerov, Georgi (Bulgaria : SIF, 1978)
The successful writer Dobrin Iliev must take part in a literary competition as a chief of jury. Guided by her great desire to win, young schoolgirl Maya manages to become friendly with him. Her expansive personality appeals to him and it stirs his dormant feelings. What is more, he likes the poems of the provocative girl. Aware of the writer's weakness for her, Maya tells him of her secret: she is Katya`s daughter. Twenty-five years ago Katya used to send him inspired poems to the front while she was still a student. Dobrin Iliev recalls his youth, when he works on pooling of private farms into big collective farms, when he had passed over with indifference the feelings of the sincere idealist Katya. Maya's mother almost gets married to a young poet, at the time an employee of a cultural propaganda unit, but at the last moment Dobrin escapes. Maya tries to convince Dobrin Iliev that she is his daughter and he is obliged to support her career. He knows full well that he is not Maya's father, but he nevertheless decides to help her and Maya gets the first prize in the school competition. However, it turns out that the poems belong to another girl, her schoolmate (Petya Dubarova, indeed a renowned poetess in Bulgaria). Against the background of Maya's swap of art for falsehood, Dobrin Iliev becomes aware of similar falsehoods in his and society's life.
Keywords: Fiction films